MODELING OF THE HEAT AND MASS TRANSFER IN DRYING OF FERMENTED CACAO (THEOBROMA CACAO L.) BEANS - Perez, Jonathan (Food and Feed Research, 2026)
A three-dimensional finite element model consisting of 108 cacao beans was developed to simulate heat and mass transfer during forced convection drying. The model evaluated temperature distribution within the drying chamber and individual beans as influenced by airflow, while physical and thermodynamic properties were computed and applied within the simulation. Model performance was validated experimentally, showing good agreement between simulated and observed moisture and temperature profiles. Moisture content data yielded RMSE values of 2.538 and 2.221 g water/g dry matter, while temperature RMSE ranged from 2.19–3.30 °C at 50 °C and 2.78–3.62 °C at 60 °C, indicating acceptable deviation. Results showed that beans positioned at the tray edges and upper layers exhibited higher internal temperatures than those in the bottom layer. These findings suggest that rearranging beans 60–90 minutes into the drying process may enhance drying uniformity and product quality. The presented 3D multi-bean model constitutes a significant advancement over traditional single-seed modeling approaches and provides a useful tool for optimizing cacao drying processes, with potential applicability at industrial scale.